Ghrelin, adipokines, metabolic factors in relation with weight status in school-children and results of a 1-year lifestyle intervention program. Issue 1 (December 2015) - Rambhojan, Christine; Bouaziz-Amar, Elodie; Larifla, Laurent; Deloumeaux, Jacqueline; Clepier, Josiane; Plumasseau, Jean; Lacorte, Jean-Marc; Foucan, Lydia
Abstract Background Overweight in Guadeloupe is a public health matter affecting children and adults. In the present study we evaluated the metabolic profile, including serum ghrelin, leptin and adiponectin levels, in normal weight, overweight and obese school children and we analyzed the potential changes in anthropometric and metabolic risk factors after a 1-year lifestyle intervention program. Methods Parameters were assessed at baseline and at 1 year. Three groups (G) were defined according the International Obesity Task Force reference values, G1: normal weight / G2: overweight / G3: obese. The lifestyle intervention included dietary counseling, regular physical activity and family support. Results A total of 120 children (G1:n = 44, G2:n = 39, G3:n = 37), aged 11– 15 years and 59 % girls were enrolled. Obese children showed significant lower HDL-C, adiponectin and ghrelin concentrations, higher triglycerides, fasting blood glucose, insulin and leptin levels and also higher frequencies of abdominal obesity (G1: 2.3 %, G2: 28.2 %, G3: 73 %) and insulin resistance (GI: 39 %, G2: 72 %, G3: 89 %) than the other groups. In the overall sample, the linear regressions exploring the associations of ghrelin, adiponectin and leptin with age, gender, BMI z-score, HOMA-IR and tanner stage as independent variables showed strong associations of leptin levels with weight status and insulin resistance at baseline. The models accounted for 58 % of variability in leptin levels compared with 26 and 15 % for adiponectin and ghrelin levels respectively. In 83 children who completed the program, significant decreases in BMI z-score in overweight and obese children were noted. Leptin levels decreased significantly only in the obese group whereas adiponectin concentrations increased significantly in the three groups, In obese children, a significant correlation was found between changes in BMI Z-score, and changes in leptin levels (r = 0.39;P = 0.049) but not with changes in adiponectin levels. Conclusions Abdominal obesity and insulin resistance were highly prevalent in obese children highlighting their risk of metabolic complications in adulthood. A 1-year long lifestyle intervention was associated with improvement in BMI z-score and metabolic parameters.